Default Rates in the Loan Market for SMEs: Evidence from Slovakia - Jarko Fidrmuc; Christa Hainz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
The current crisis raises the question whether loans to SMEs in emerging markets areinherently more risky. We use a unique unbalanced panel of nearly 700 loans made toSMEs in Slovakia between 2000 and 2005. Several probit and panel probit models showthat liquidity and profitability factors are important determinants of SME defaults.Moreover, we find that indebtedness significantly increases the probability of default.Finally, liability as proxied by the legal form of SMEs has important incentive effects.In sum, default rates and factors converged to values found in developed financialmarkets.
Keywords: C25; G21; G33; 330; SMEs; banking; loan default; incentives; asymmetric information; probit; financial crisis